2010
DOI: 10.1073/pnas.0912176107
|View full text |Cite
|
Sign up to set email alerts
|

ACTH protects against glucocorticoid-induced osteonecrosis of bone

Abstract: We report that adrenocorticotropic hormone (ACTH) protects against osteonecrosis of the femoral head induced by depot methylprednisolone acetate (depomedrol). This therapeutic response likely arises from enhanced osteoblastic support and the stimulation of VEGF by ACTH; the latter is largely responsible for maintaining the fine vascular network that surrounds highly remodeling bone. We suggest examining the efficacy of ACTH in preventing human osteonecrosis, a devastating complication of glucocorticoid therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
138
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 134 publications
(142 citation statements)
references
References 34 publications
3
138
1
Order By: Relevance
“…(40) Interestingly, increased osteoblast apoptosis and resulting loss of vascular endothelial growth factordependent angiogenesis support has been implicated in humans and in animal models of AVN receiving glucocorticoids. (41)(42)(43) Osteoblastic dysfunction (17) and abnormalities of mesenchymal stem cells (44) have been described in animal models of GD and in a human patient, respectively. Both these cell types are essential components of the hematopoietic microenvironment, and dysfunction of either or both could conceivably link AVN and anemia as secondary phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…(40) Interestingly, increased osteoblast apoptosis and resulting loss of vascular endothelial growth factordependent angiogenesis support has been implicated in humans and in animal models of AVN receiving glucocorticoids. (41)(42)(43) Osteoblastic dysfunction (17) and abnormalities of mesenchymal stem cells (44) have been described in animal models of GD and in a human patient, respectively. Both these cell types are essential components of the hematopoietic microenvironment, and dysfunction of either or both could conceivably link AVN and anemia as secondary phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that as with the adrenal cortex, ACTH induces Vascular endothelial growth factor (VEGF) production in osteoblasts through its action on MC2Rs [87]. This likely translates into the protection by ACTH of glucocorticoidinduced osteonecrosis in a rabbit model [87].…”
Section: Adrenocorticotrophic Hormonementioning
confidence: 99%
“…osteoporosis | osteoblast | skeleton O ver the past decade, we have described direct actions of anterior and posterior pituitary hormones on the skeleton (1)(2)(3)(4)(5)(6)(7)(8). We have shown that these actions are exerted via G protein-coupled receptors resident on both osteoblasts and osteoclasts.…”
mentioning
confidence: 99%
“…Apart from the known actions of growth hormone on the skeleton, Tsh, Fsh, Acth, Oxt, and vasopressin (Avp) have all been shown to regulate the formation and/or function of both osteoblasts and osteoclasts and thus to control bone remodeling in vivo (2)(3)(4)(6)(7)(8). The two neurohypophyseal hormones Oxt and Avp have opposing functions (2,3).…”
mentioning
confidence: 99%